2016
DOI: 10.1093/ofid/ofw150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact on Tuberculosis Treatment Outcomes of Discordance Between Molecular and Growth-Based Assays for Rifampin Resistance, California 2003–2013

Abstract: Background. Data from international settings suggest that isolates of Mycobacterium tuberculosis with rpoB mutations testing phenotypically susceptible to rifampin (RIF) may have clinical significance. We analyzed treatment outcomes of California patients with discordant molecular-phenotypic RIF results.Methods. We included tuberculosis (TB) patients, during 2003–2013, whose specimens tested RIF susceptible phenotypically but had a rpoB mutation determined by pyrosequencing. Demographic data were abstracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
6
21
0
Order By: Relevance
“…In contrast, a portion of the isolates with intermediate resistance and substitutions in codons 516 and 526 were identified as susceptible by Bactec MGIT 960, which was in line with previous reports [12]. Previous reports noted the clinical importance of “disputed” mutations in the rpoB gene [34, 35, 36]. Because the standard treatment of these patients might result in a poor clinical outcome [37, 38], the use of higher doses of RMP [25] or substitution with RFB [39] is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a portion of the isolates with intermediate resistance and substitutions in codons 516 and 526 were identified as susceptible by Bactec MGIT 960, which was in line with previous reports [12]. Previous reports noted the clinical importance of “disputed” mutations in the rpoB gene [34, 35, 36]. Because the standard treatment of these patients might result in a poor clinical outcome [37, 38], the use of higher doses of RMP [25] or substitution with RFB [39] is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the most common pattern of discrepancy was genotypic susceptibility and phenotypic resistance to INH, which is a similar to findings reported from the USA (14,26). This phenomenon is reasonable because whereas MTBDRplus test can detect specific mutations at katG and inhA genes, 20% of INH resistance is known to be developed by mutations at regions other the above two genes, such as ahpC gene (27).…”
Section: Clinical Profiles and Treatment Outcome In The 63 Tb Patientsupporting
confidence: 89%
“…Clinicians usually treated these patients by replacing RIF with other drugs including an MDR regimen with a longer duration. Other reports have also shown that, in the case of RIF discordance with genotypic resistance, treatment failure develops more frequently, and an extended-duration or second-line anti-TB regimen might be more successful (14)(15)(16).…”
Section: Clinical Profiles and Treatment Outcome In The 63 Tb Patientmentioning
confidence: 97%
“…Although, the association of D516F substitution with discordant susceptibility tests was reported in previous studies [32,33], our data was not in agreement with the results of Tan et al, Berrada et al,. The occurrence of mutation D516F has been proposed to cause low-level rifampicin resistance [32,37]. Low level rifampicin resistance may influence the treatment; particularly phenotypic DST outcomes may vary from the actual effectiveness of anti-TB drugs in patients [38].…”
Section: Discussionmentioning
confidence: 99%